CONFLICT MANAGEMENT IN THE WORK ENVIRONMENT: A QUALITATIVE STUDY ON VILLAGE ECONOMIC UNITS - Sidik Budiwidodo; Eli Suherli; Agus Rohmat Hidayat; Farika Chandrasari (Politeknik Siber Cerdika Internasional, 2024)
Work conflict is a common dynamic in organizations, including in village economic units such as Village-Owned Enterprises (BUMDes). This research aims to deeply understand the sources of conflict, resolution strategies, as well as the supporting and inhibiting factors of conflict management in the BUMDes environment. Using a descriptive qualitative approach, data was collected through in-depth interviews and participatory observation of BUMDes managers and members in rural areas. The results show that conflicts in BUMDes are generally caused by generational differences, authoritarian leadership style, unclear tasks, and lack of formal conflict resolution system. Effective conflict resolution strategies tend to be participatory and based on village deliberation, with the village head or community leaders playing an important role as mediators. These findings contribute to designing a locally-based conflict resolution approach to strengthen sustainable village economic institutions.